Application of the method of moments in the probabilistic theory of numbers - Misevičius, G. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Г. Мисявичюс. Применение метода моментов в вероятностной теории чисел G. Misevičius. Momentų metodo panaudojimas tikimybinėje skaičių teorijoje